Transformational Leadership and Psychological Needs of Employees - Ivana Bojović; Sandra Stojadinović Jovanović (Technium Social Sciences Journal, 2020)
Transformational leadership theory is an essential topic in management research. This style of leadership requires a leader’s ability to identify and observe the psychological needs and values of followers, as well as to stimulate work motivation. Transformational leadership is characterized by four groups of factors: individualized consideration, intellectual stimulation, inspirational motivation and charisma or idealized influence. The role of a transformational leader is motivational in nature. Within the theory of self-determination, the authors emphasize the importance of the basic psychological need for relatedness with others, the feeling of personal competence and autonomy in performing a given behavior. Recent research has shown that perceived transformational leadership contributes to meeting the basic psychological needs of employees. Satisfying each of these needs directly impacts positive outcomes and achievement of organizational goals. The most commonly reported positive outcomes include trust of employees in the organization, positive feedback from managers, belief in one’s own ability to contribute to the organization, recognizing opportunities for progress, feeling of security, job satisfaction and a high level of enthusiasm for work. Transformational leadership facilitates the adoption of common motivational principles in the organization, empowers managers and gains the support of followers in their efforts to build a strong and stable organizational culture.